Adaptive responses to directional trait selection in the Miocene enabled Cape proteas to colonize the savanna grasslands - Lamont, Byron; He, Tianhua; Downes, Katherine (Kluwer Academic Publishers, 2013)
Directional selection occurs when the agent of selection changes direction or strength such that fitness of a dominant trait is relaxed or even annulled, and simultaneously the fitness of a rare opposing trait is intensified or even becomes essential. The value of this concept in evolutionary ecology was demonstrated by mapping fire- and growth-related traits and regional affinity onto a molecular-based chronogram for 91 species of Protea that is widespread in the shrubland and grassland biomes of southern Africa. The crown clade arose 22–34 million years ago (Oligocene) in the Cape shrublands that was increasingly winter wet, nutrient and water-limited, and moderately fireprone. This environment favoured nonsprouting and resprouting shrubs, on-plant seed storage (serotiny) and strong sclerophylly. Adjoining grasslands developed 7–19 million years ago (mid-late Miocene) that were summer wet, carbon-limited and highly fireprone. This favoured resprouting only, seed release at maturity, and taller plants with large leaves and weak sclerophylly.Thus, for successful migration from the shrublands to grasslands, the dominant ancestral condition of serotiny was replaced by almost universal nonserotiny in response to a change in fire type, and the dominant ancestral condition of nonsprouting by universal (lignotuberous) resprouting in response to more frequent fire. Taller plants with epicormic resprouting and larger, softer leaves were also promoted, due to the change in fire type, growing season and declining pCO2, but appeared 4–6 million years later. Thus, adaptive radiation via directional selection in the novel grassland environment required a suite of adaptive responses to various selection pressures that led to species radiation in the vast habitat available now constrained by stabilizing selection. The biology of grasses in savanna grasslands may well have changed during the Miocene/Pliocene but so did the woody plants that invaded them.